Time-of-flight mass spectrometry - Price, Dennis; Williams, John Edward, 1925- (Pergamon Press, 1969)
Time-of-Flight Mass Spectrometry contains the proceedings of the First European Symposium on Time-of-flight Mass Spectrometry held at the University of Salford in the UK on July 3-5, 1967. The papers focus on time-of-flight mass spectrometry and its chemical applications, from flash photolysis and pyrolysis reactions to shock wave reactions and high-temperature studies of inorganic solids. This book is comprised of nine chapters and opens with an introduction to the MA-1 and other time-of-flight mass spectrometers, followed by their applications to studies of chemical reactions such as flash p.